2022
DOI: 10.7717/peerj-cs.959
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical COVID-19 model with vaccination: a case study in Saudi Arabia

Abstract: The discovery of a new form of corona-viruses in December 2019, SARS-CoV-2, commonly named COVID-19, has reshaped the world. With health and economic issues at stake, scientists have been focusing on understanding the dynamics of the disease, in order to provide the governments with the best policies and strategies allowing them to reduce the span of the virus. The world has been waiting for the vaccine for more than one year. The World Health Organization (WHO) is advertising the vaccine as a safe and effecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…By the fifth phase of COVID-19, approximately 81% of the Thai population received at least one vaccination, 73% received two vaccinations, and 36% received a third vaccination [ 29 ]. However, coverage has been inconsistent throughout Thailand, with much lower vaccination rates among people living in remote areas [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…By the fifth phase of COVID-19, approximately 81% of the Thai population received at least one vaccination, 73% received two vaccinations, and 36% received a third vaccination [ 29 ]. However, coverage has been inconsistent throughout Thailand, with much lower vaccination rates among people living in remote areas [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the speed of vaccination became more important with a higher reproductive number, potentially resulting in many more deaths. Further, in 2022, studies by Arshad et al [ 33 ] in Tunisia and Algarni et al [ 34 ] in Saudi Arabia demonstrated the benefits of a comprehensive vaccination campaign in reducing deaths and infections associated with COVID-19 [ 33 ] and identified the vaccination rate as a crucial factor in controlling virus spread [ 34 ]. Many studies have yet to establish criteria for assessing the effectiveness of different types of vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…Some other features of COVID-19 that are not considered are the immunity development by vaccinated individuals and the immunity loss by the recovered people. It has been observed that this phenomenon occurs in many epidemic models as well (see, for instance 26 , 27 , 32 ,).…”
Section: Introductionmentioning
confidence: 89%